USAHA SANGGAR SENI DIDIK NINI THOWOK DALAM MENEMBUS PASAR - Sutiyono Sutiyono (LPPM UNY, 2002)
Abstract The purpose of the research is to know the effort of Sanggar Seni Didik Nini Thowok Yogyakarta as nonformal art educational program in marketing perforate. Data was obtained through a bibliographical study, observation, interviews and documentary study. Approach of the research is used to qualitative approach. The result of this study showed that the efforts is done by Sanggar Seni Didik Nini Thowok Yogyakarta is: (1) to order sanggar management, (2) to stand at attention of discipline, and (3) publication/promotion of sanggar name. Keywords:art, sanggar, effort